1978
DOI: 10.4141/cjps78-029
|View full text |Cite
|
Sign up to set email alerts
|

Dry Weight, Soluble Sugar Content, and Starch Content of Maize Kernels During the Early Postsilking Period

Abstract: Torr-rNlen, M. eNo DevNeno, T. B. lg7g. Dry weight, soluble sugar conrenr, and starch content of maize kemels during the eaily poitsilking period. can. J.Plant Kernel development was studied in the maize (Zea mays L.) hybrids united-Hl06 and Funk's G-4444, grown in a controlled-environment growth rlom. A method was employed in which husks were excised, and kernels weri removed from the same set of ears at several subsequent sampling dates. This method did not affect the dry. matter accumulation of the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 10 publications
3
24
0
1
Order By: Relevance
“…In maize, different treatments have been applied to increase the source-sink ratio relative to a control, but the approaches used were always difficult to be interpreted. The degraining treatment we imposed is novel, as it (i) did not alter the distribution of grains of different hierarchies in the ear, and (ii) had placebos, evidencing that there were no noticeable negative collateral effects of the treatments on the growth of the remaining grains (which considerably extends previous evidence that removing the husks did not affect grain weight; Tollenaar and Daynard, 1978). Both changes in plant density and controlled pollination (bagging ears at silking) may also affect grain weight potential, and then differences in grain size at maturity may better reflect these effects on grain size potential than the degree of source or sink limitation during the effective grain-filling period.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In maize, different treatments have been applied to increase the source-sink ratio relative to a control, but the approaches used were always difficult to be interpreted. The degraining treatment we imposed is novel, as it (i) did not alter the distribution of grains of different hierarchies in the ear, and (ii) had placebos, evidencing that there were no noticeable negative collateral effects of the treatments on the growth of the remaining grains (which considerably extends previous evidence that removing the husks did not affect grain weight; Tollenaar and Daynard, 1978). Both changes in plant density and controlled pollination (bagging ears at silking) may also affect grain weight potential, and then differences in grain size at maturity may better reflect these effects on grain size potential than the degree of source or sink limitation during the effective grain-filling period.…”
Section: Discussionsupporting
confidence: 62%
“…This treatment would be critical in combination with heat stress to conclude whether any heat effects on grain growth are direct (on the capacity of grains to grow) or indirect (through reducing source strength by accelerating senescence). Tollenaar and Daynard (1978) and Gambín et al (2007) proved the feasibility of degraining treatments in maize, but, as mentioned above, their analysis was not focused on the effects of source-sink relationship on yield components. Jones and Simmons (1983) and Kiniry et al (1990) attempted a direct manipulation of sink strength by simply cutting the ear and removing the apical half at different days after silking.…”
Section: Hybrids Nitrogen Fertilization Regimes and Heat Stress Trementioning
confidence: 99%
“…3). The balance of TEC presumably was starch (22). TEC were lower in leaves, stems, and reproductive stalks of -H20 plants relative to controls on d 6 (Fig.…”
Section: Developmentmentioning
confidence: 90%
“…Aborting kernels from cob pieces containing all 6 kernels may actually be more representative of aborting kernels from the tips of ears grown in the field than are kernels induced to abort by high temperature. Tollenaar and Daynard (20) found that aborting kernels from the tips of ears grown in the field also continued to accumulate starch even after the cessation of dry matter accumulation. Low assimilate supply may have prevented the aborting kernels cultured 6/cob piece from entering a period of linear dry matter accumulation.…”
Section: Days After Pollinationmentioning
confidence: 97%